On the challenges associated with the study of police use of deadly force in the United States: A response to Schwartz & Jahn - Nix, Justin (2020)
In response to Gabriel Schwartz and Jaquelyn Jahn’s descriptive study, “Mapping fatal police violence across U.S. metropolitan areas: Overall rates and racial/ethnic inequalities, 2013–2017,” I provide three reflections. First, the framing of this issue is vitally important. Second, police-involved fatalities represent a nonrandom sample of all incidents involving police use of deadly force (i.e., physical force that causes or is likely to cause death), and unfortunately, we lack comprehensive data on use of deadly force that does not result in fatalities. Finally, to make sense of who is killed by the police, researchers must also identify who was exposed to the risk of being killed by the police